2018
DOI: 10.21608/jfds.2018.36100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Taro Corms on Functional Low Fat Ice Cream Properties

Abstract: The influence of adding Taro corms ( Colocasia esculenta L. ) on the physico-chemical, rheological, and organoleptic properties. Moreover, antioxidant compounds present in ice cream mixtures, and their resultant frozen products was studied. Taro corms , whether fresh or boiled, was added (partial substitute of ice cream mix), at a levels of 10, 20, and 30% , to the mixtures of the experimental treatments, after reducing their fat contents to 4%, and stabilizer/emulsifier mixture to 0.175 % , while the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…CPP contains a high amount of fiber which able to gelatinize and therefore, increase the viscosity and flow time under the processing conditions of frozen yoghourt mix. Similar results were found by 13,14 . T1,2,3 treatments with fortified carrot pomace powder 5,10,15% respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…CPP contains a high amount of fiber which able to gelatinize and therefore, increase the viscosity and flow time under the processing conditions of frozen yoghourt mix. Similar results were found by 13,14 . T1,2,3 treatments with fortified carrot pomace powder 5,10,15% respectively.…”
Section: Resultssupporting
confidence: 91%
“…The dried carrot pomace has carotene and ascorbic acid, and is also a rich source of fiber, antioxidants, minerals including calcium, copper, magnesium, potassium, phosphorus, iron and folic acid which exhibit health promoting effects 44. Regarding the nutritional quality and high fiber content of CPP, it has been used to enrich some foods including durum wheat pasta 18 and wheat flour biscuits 29. Also, the nutritional and health importance of fiber-rich foods has been clarified 43. The pomace, a cause of environmental pollution may be converted to value added products, if processed properly 37 . Being fiber rich, the pomace may be incorporated into food products as inexpensive, non-caloric bulking agents for partial replacement of product component, fat or sugar, as enhancers of water and oil retention and to improve emulsion or oxidative stabilities 11,14 .…”
Section: Introductionmentioning
confidence: 99%
“…GCSP is known to contain a high amount of starch fiber which is able to gelatinize during the US and therefore, may increase the viscosity and flow time of the ice milk mix. Similar results were reported by El-Dardiry and Gab-Allah (2016) and El-Dardiry et al, 2018). Also, the gum present in the GCSP led to an increase in viscosity and flow time in the treatments.…”
Section: Results Of Ice Milk MIXsupporting
confidence: 89%
“…The lower freezing point in treatments with GCSP could be due to its higher lactose and ash contents. The freezing point is affected by the amount, type and molecular weight of the solutes in the mix (Marshall et al, 2003;El-Dardiry et al, 2018). It was also found that the control treatment with ultrasonic (C 2 ) led to a lower freezing point than the control-treated with pasteurization (C 1 ).…”
Section: Results Of Ice Milk MIXmentioning
confidence: 96%
“…The H-ORAC (Hydroxyl Radical Antioxidant Capacity), ABTS (2,2′-Azino-bis[3-ethylbenzothiazoline-6-sulfonic acid] diammonium salt), FRAP (ferric reducing antioxidant power), and DPPH (2,2′-diphenyl-1-picrylhydrazyl radical assay) methods have been applied to evaluate the TAC of taro extracts or taro-food derivatives. Flavonoids, tannins, saponins, alkaloids, carotenoids, phenols, vitamins, and fatty acids seem to contribute to overall taro antioxidant capacity ( Table 3 ) [ 13 , 52 , 53 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ].…”
Section: Bioactive Compounds and Pharmacological Properties Of Tarmentioning
confidence: 99%